CORRELATION OF SLAKE DURABILITY INDEX WITH UNCONFINED COMPRESSIVE STRENGTH ESTIMATED THROUGH INDIRECT METHODS FOR CARBONATE ROCKS OF SALT RANGE, PAKISTAN - Arslan, M.; Khan, M. S. (The Nucleus, 2014)
In evaluation of engineering behavior of rock mass and rock materials, slaking of rocks is an important consideration. For the construction industry, a durable rock is usually preferred. About 75% of the rocks outcropping on continents are sedimentary rocks. To determine rock strength and deformation, direct tests such as uniaxial compressive strength are expensive and require considerable time. Hence there is need to explore relations through other indirect methods such as Slake Durability Index, Point Load Strength and Schmidt rebound hammer test. To investigate the correlation between Slake Durability and strength, multidisciplinary approach was adopted. For this study, one of the important industrial rock groups belonging to carbonate geology of Salt Range was selected. The Slake Durability Index test was performed on 32 rock samples collected from different parts of Salt Range and the test results were compared with indirect strength such as Point Load Strength and Schmidt Hammer Hardness. Data was statistically analyzed through linear regression analysis to determine the correlation coefficient and the variability of results for each test. A strong linear correlation of 1st cycle Slake Durability Index exists with Point Load Strength and Schmidt Hammer Hardness.